Antibody response in patients with autoimmune inflammatory rheumatic disease after pneumococcal polysaccharide prime vaccination or revaccination. (4th March 2023) - Rasmussen, SL; Strandbygaard, LL; Fuursted, K; Kragholm, KH; Leutscher, P; Rasmussen, C
Abstract : Objective: The aim of the study was to assess the pneumococcal antibody response in autoimmune inflammatory rheumatic disease (AIIRD) patients receiving 23-valent pneumococcal polysaccharide vaccine (PPV23) as a prime vaccination or revaccination. Method: Antibodies to 12 serotypes occurring in the commonly applied pneumococcal vaccines in Denmark were measured in AIIRD patients receiving biological disease-modifying anti-rheumatic drug (bDMARD) treatment for rheumatoid arthritis, spondyloarthritis, or psoriatic arthritis. Patients with a non-protective level of pneumococcal antibodies (geometric mean pneumococcal antibody level < 1 μg/mL) were invited to receive vaccination with PPV23 followed by control of antibody titre 3 months later. Results: In total, 224 (74%) of 301 patients were included in the analyses, of whom 126 patients had previously received PPV23 vaccination. Post-vaccination antibody measurement revealed that only 80 patients (36%) achieved a protective level of antibodies. In a multivariable logistic regression analysis, significantly more patients without a previous PPV23 vaccination history achieved a protective antibody level compared with patients with a history of PPV23 vaccination less than 5 years ago (p = 0.005). This difference was not seen when comparing the former group with patients vaccinated 5 years ago or more. Methotrexate (MTX) treatment at the time of vaccination was associated with a non-protective antibody level (p < 0.001). Conclusion: Only 36% of patients with a non-protective antibody level achieved a protective level in response to pneumococcal vaccination. Pneumococcal vaccination within the last 5 years and MTX treatment at the time of vaccination were independently associated with a poor antibody response.